Numerical Analysis of the Bridge Orthotropic Deck Time Dependent Resistance - Vican, Josef; Sykora, Marian (Communications - Scientific letters of the University of Zilina, 2013)
Resistance of the stiffened plated orthotropic deck of bridge with ballast bed is affected by the environmental action effects due to unchecked corrosion process of steel bridge deck under ballast bed. Therefore, to observe the behaviour and resistance of those types of steel bridges, the probabilistic nonlinear finite element analysis using adequate sophisticated software is needed. The paper presents results of the parametric numerical analysis of the time dependent resistance of bridge with ballast bed on the orthotropic deck considering corrosion attack using ANSYS software support module PDS. Random variables entering calculations were described by means of parameters of probability density functions according to data determined experimentally. The model takes also into account the geometrical and material nonlinearities of bridge structure including the selected corrosion models.